Presencia de Marcial en Los Epigramas de León de Arroyal (1784) - Moreno Soldevila, Rosario (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
Martial’s influence on León de Arroyal’s epigrams, published in 1784, is not restricted to his imitation of particular poems. This paper focuses on the various ways in which the Latin poet pervades Arroyal’s epigrammatic work.